The sense of the universe : philosophical explication of the theological commitment in modern cosmology - Nesteruk, Alexei V. (Fortress Press, 2015)
The Sense of the Universe deals with existential and phenomenological reflection upon modern cosmology with the aim to reveal hidden theological commitments in cosmology related to the mystery of human existence. The book proposes a new approach to the dialogue between science and theology based in a thorough philosophical analysis of acting forms of subjectivity involved in the study of the world and in religious experience. The book contributes to the synthesis of appropriation and incorporation of modern philosophical ideas in Christian theology, in particular its Eastern Orthodox form.